(untitled) (Eurasian Journal of Ecology, 2023)
The study is devoted to the scientific substantiation of the methodology for the commercial production of saigas in the Volga-Zhaiyk interfluve, the number of which reached 801,000 heads according to the results of spring accounting in 2022, which is comparable, for example, to the number of sheep and goats grazing in this area (752,300 heads). The results of determining the regional resource potential (capacity) of rangelands, taking into account the number of species (cattle, sheep, goats, horses and camels) and the average annual area of grazing rate per head are presented. Two periods characterized by extensive use of pastures in this region with self-regulation of the number of herbivorous animals were compared: in the era of the Bukeyev Khanate, which occupied these very territories (1838) and in the modern period of formation of private farms (2022). It has been shown that up to 2.0 mln head of livestock were grazing on this area in total, with 1.5 times less than in 1839, and that in the modern period saigas needed around 10 mln ha of grazing land on average (taking into account the grazing rate of each species). In addition, another 1.5 million hectares of rangeland are now needed for saigas. The total area of the study area is about 12.3 mln ha. As we can see, the proposed methodology shows comparable results on the capacity of the rangelands between the Volga and Zhaik rivers in different periods, which indicates that it can be used for mathematical rather than empirical calculations of the artificial regulation of the saiga population. In addition, the variability of limiting factors of the natural environment (food and water), which is subject to climatogenic transformation, should be taken into account in their industrial production. Key words: saigas of the Ural population, animal fishery, pasture capacity, farm animals.